Modelling Chloris virgata germination and emergence under different temperature and light quality conditions - Rodriguez, Sebastián (2020)
Chloris virgata is a problematic weed around the world. Prediction of weed germination rates could be a useful strategy to optimise timing of weed control actions. We studied the germination and emergence of C. virgata collected seeds under different after‐ripening treatments and different exhumation dates after seed dispersal, to estimate seed dormancy level and predict weed emergence dynamics under field conditions. Three experiments were conducted under controlled conditions to determine base, optimum and maximum germination temperatures (T b, T o and T m respectively) and comprised: (a) exposure of seeds to gradually increasing and decreasing temperatures between 5 and 35°C; (b) exposure of seeds to different constant temperatures; and (c) exposure of seeds to different light quality conditions (red ? far red ratio) and temperature regimes (constant and alternating temperatures). To explore genuine environmental conditions, a field experiment was performed to determine weed emergence under different shading levels. Finally, with the data obtained, a thermal time model for dormancy release was used to predict C. virgata seedling emergence in the Argentine Pampas region. Seeds after‐ripened in cold and wet conditions and constant 25°C showed the highest germination percentages. The values of T b (7°C), T o (28°C) and T m (40°C) remained constant at all exhumation dates. Neither light quality nor thermal regime modified the final germination percentages. However, shading delayed seedling emergence under field conditions, even when it was adjusted by thermal time. These results may allow predicting C. virgata emergence in temperate regions and help to improve weed control in integrated weed management strategies.